2020
DOI: 10.3390/biology9120460
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Acidosis Associated with Ischemic Stroke to Guide Neuroprotective Drug Delivery

Abstract: Ischemic stroke is a leading cause of death and disability worldwide. Yet, the effective therapy of focal cerebral ischemia has been an unresolved challenge. We propose here that ischemic tissue acidosis, a sensitive metabolic indicator of injury progression in cerebral ischemia, can be harnessed for the targeted delivery of neuroprotective agents. Ischemic tissue acidosis, which represents the accumulation of lactic acid in malperfused brain tissue is significantly exacerbated by the recurrence of spreading d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 120 publications
1
42
0
Order By: Relevance
“…Waves of spreading depolarization result in transient, but long-lasting acidification of the ischemic cortex of rats [ 165 ]. Acidosis accompanying ischemia is a harmful event, reducing astrocyte glutamate uptake [ 166 ] and exacerbating cytotoxic edema and cellular damage [ 167 ]. When exposed to a low extracellular pH, astrocytes are unable to maintain their pH above 7, but acidify and may even undergo cell death [ 159 , 162 , 168 ].…”
Section: Relevance Of Astrocytic Cation Homeostasismentioning
confidence: 99%
“…Waves of spreading depolarization result in transient, but long-lasting acidification of the ischemic cortex of rats [ 165 ]. Acidosis accompanying ischemia is a harmful event, reducing astrocyte glutamate uptake [ 166 ] and exacerbating cytotoxic edema and cellular damage [ 167 ]. When exposed to a low extracellular pH, astrocytes are unable to maintain their pH above 7, but acidify and may even undergo cell death [ 159 , 162 , 168 ].…”
Section: Relevance Of Astrocytic Cation Homeostasismentioning
confidence: 99%
“…The intranasal administration of nanoparticles can accumulate their cargo in the brain unlike systemic free administration [124]. Moreover, some nanoparticles release their cargo only in an acidic environment, which is a characteristic of ischemic tissue at risk of irreversible damage; this molecular design allows the enriching of acutely injured tissue without the risk of unfavorable off-target effects [125]. These new technological breakthroughs are a major step forward in specifically targeting injured cerebral tissue with drugs that interfere with DAMPs and PPRs.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…In hypoxic/anoxic conditions, in vitro studies have shown a decrease in pH in neurons and glial cells [ 11 ]. Brain acidosis itself causes neuronal injury by generating free radicals, affecting glutamate reuptake, glial cell activation and neuronal apoptosis [ 12 , 13 ] and exacerbates ischemic brain injury [ 14 , 15 ] leading to cerebral infarction such as edema and blood-brain barrier (BBB) dysfunction [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%